Nilai Dakwah dalam Film Qodrat Tentang Kajian Tauhid dalam Perspektif Semiotika Ferdinan De Sausure - Izus Salam (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. In carrying out his daily life every individual will be faced with various differences that cannot be avoided, one of these differences is religious differences. In the context of da'wah in the digital era, the values of da'wah are visualized in the form of films that attract more attention, such as the film Qodrat which has a message with the aim of this research. the value of monotheism in each activity, this is in line with the method used in this paper using qualitative methods with a descriptive approach. Qualitative methods are used to answer questions about